Radio Nation : Communication, Popular Culture, and Nationalism in Mexico, 1920-1950 - Hayes, Joy Elizabeth, 1966- (Book collections on Project MUSE., 2020)
"More than narrative history, Hayes's study provides an analytical framework for understanding the role of radio in building Mexican nationalism at a critical time in that nation's history. Radio Nation expands our appreciation of an overlooked medium that changed the course of an entire country."--Jacket.